2020
DOI: 10.1128/mbio.01578-20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nuclear Export Pathway on Cytoplasmic HIV-1 RNA Transport Mechanism and Distribution

Abstract: HIV-1 full-length RNA (referred to as HIV-1 RNA here) serves as the viral genome in virions and as a template for Gag/Gag-Pol translation. We previously showed that HIV-1 RNA, which is exported via the CRM1 pathway, travels in the cytoplasm mainly through diffusion. A recent report suggested that the export pathway used by retroviral RNA could affect its cytoplasmic transport mechanism and localization. HIV-1 RNA export is directed by the viral protein Rev and the cis-acting element, Rev response element (RRE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…How does cap exposure prevent packaging? The inability of HIV-1 Gag proteins to package cap-exposed viral RNAs is not likely due to altered intracellular trafficking since live-cell imaging studies have shown that both translating and nontranslating pools of HIV RNAs actively transit sites of virus assembly ( 48 , 49 ). Retroviral transcripts involved in translation and packaging exist in separate, noninterconverting pools ( 22 , 48 51 ), and splicing of HIV-1 RNAs transcribed with three 5′ guanosines, which adopt a cap-exposed conformation, occurs at significantly greater levels than those transcribed with a single 5′ guanosine that are known to adopt a cap-sequestered conformation ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How does cap exposure prevent packaging? The inability of HIV-1 Gag proteins to package cap-exposed viral RNAs is not likely due to altered intracellular trafficking since live-cell imaging studies have shown that both translating and nontranslating pools of HIV RNAs actively transit sites of virus assembly ( 48 , 49 ). Retroviral transcripts involved in translation and packaging exist in separate, noninterconverting pools ( 22 , 48 51 ), and splicing of HIV-1 RNAs transcribed with three 5′ guanosines, which adopt a cap-exposed conformation, occurs at significantly greater levels than those transcribed with a single 5′ guanosine that are known to adopt a cap-sequestered conformation ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inability of HIV-1 Gag proteins to package cap-exposed viral RNAs is not likely due to altered intracellular trafficking since live-cell imaging studies have shown that both translating and nontranslating pools of HIV RNAs actively transit sites of virus assembly ( 48 , 49 ). Retroviral transcripts involved in translation and packaging exist in separate, noninterconverting pools ( 22 , 48 51 ), and splicing of HIV-1 RNAs transcribed with three 5′ guanosines, which adopt a cap-exposed conformation, occurs at significantly greater levels than those transcribed with a single 5′ guanosine that are known to adopt a cap-sequestered conformation ( 52 ). These findings are collectively consistent with a mechanism in which HIV-1 transcripts containing an exposed 5′ cap are irreversibly sequestered by the cellular processing and translation machinery prior to becoming accessible for Gag-dependent packaging, and that gRNAs avoid this capture by structural sequestration of their 5′ cap ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, one report found that by replacing the RRE in HIV-1 gRNA with multiple copies of the CTE, the subcellular location of the RNA was altered from a diffuse cytoplasmic pattern to one that clustered near the centrosome, suggesting that the mode of nuclear exit indeed determines the subcellular fate of the RNA [ 7 ]. However, Chen and colleagues readdressed this question by comparing the distribution of HIV-1 RNAs exported through the CRM1 or NSF1 pathway using live cell imaging [ 8 ]. They found that CTE-containing HIV-1 RNA and RRE-containing HIV-1 RNA exhibited a similar cytoplasmic distribution and did not observe clustering near the centrosome.…”
Section: Hiv-1 Genomic Rna Nuclear Export and Traffickingmentioning
confidence: 99%
“…Comparing retroviral gRNA exported by different pathways can provide further insights into potential linkage(s) of these processes. For example, HIV-1 gRNAs exported by the CRM1 or NXF1 pathway were found to have diffusive movement in the cytoplasm, while CTE-containing RNAs diffuse more slowly than RRE-containing RNAs [ 105 ]. While the biology causing observed differences in diffusion rates is unknown, one possible explanation is that RNAs exported by different pathways are associated with different proteins that alter diffusion rates to varying extents.…”
Section: Translocation Of Grna To the Plasma Membranementioning
confidence: 99%
“…For example, components of either system could serve as a signal for a particular cytoplasmic fate. However, one study reported that changes in HIV-1 gRNA localization due to the nuclear export pathway do not change gRNA localization and that the HIV-1 gRNA was not targeted to centrosomes [ 105 ]. The differences in reported observations may involve the use of proviruses to express viral components versus transfected DNAs.…”
Section: Translocation Of Grna To the Plasma Membranementioning
confidence: 99%